If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6(a+4)=-90
We simplify the equation to the form, which is simple to understand
6(a+4)=-90
Reorder the terms in parentheses
+(+6a+24)=-90
Remove unnecessary parentheses
+6a+24=-90
We move all terms containing a to the left and all other terms to the right.
+6a=-90-24
We simplify left and right side of the equation.
+6a=-114
We divide both sides of the equation by 6 to get a.
a=-19
| 4x+5-(x-2)=90 | | 9x-4+3x=2(x+18) | | 8.2=-4g | | 275+5x=y | | 275+5=y | | 6(x-4)=27 | | -625y-184=2506y | | 6x(x+5)=9x-2-3x | | -6.25y-1.84=25.06y | | 3-3x=3(-x-7)-8x | | -6.25y-1.84=25.06 | | z=2 | | 0.2N+3=-8.6 | | 8-(2y-9)=3-3y | | -(1-r)=4r+8 | | 8x+10-10=-2x+3 | | 8x-2x=3 | | 4x-10=-16x-156 | | 17-[3+6y-4(y+5)]=-5(3y-6)-[7(y-1)-18y+21] | | 3(7-n)=48 | | -3x-8+4x=12 | | (1/5)3-2= | | 10x-7+2x-3=9x-4+2x | | -16=11+9x | | -6p+50=p-30 | | 2+2y=7 | | 2y-6=15y+111 | | 2y-6=13y+111 | | 5x-4=2(2x+3)-2 | | .78= | | 11(x+4)-2x=3(3x+4)-13 | | 11(x+4)-2v=3(3v+4)-13 |